Peripartum heart failure in Finland: A population‐based record linkage study - Antti M. Puhakka; Georg Macharey; Volker Ziller; Mika Gissler; Aydin Tekay; Corinna Keil; Denise Hilfiker‐Kleiner (ESC Heart Failure)
Abstract Aims Heart failure in late pregnancy and the postpartum period (HFPP) is a rare but potentially life‐threatening condition, with peripartum cardiomyopathy (PPCM) being the most common subtype. This study aims to comprehensively investigate the prevalence of HFPP in the Finnish population and identify the underlying risk factors associated with its occurrence. Methods We conducted a retrospective analysis using data from the Finnish Medical Birth Register and the Finnish Care Register for Health Care, covering 1996 to 2021. The dataset comprised 1 387 457 deliveries. HFPP cases were identified based on specific ICD‐10 codes. To ensure the accuracy of our findings, we excluded cases with pre‐existing cardiomyopathies and other significant cardiac diseases diagnosed before pregnancy. We employed logistic regression models to evaluate the associations between maternal factors and the incidence of HFPP. Results We identified 159 cases of HFPP, resulting in an incidence rate of 11.5 per 100 000 deliveries. This incidence is comparable with rates reported in other Scandinavian countries and lower than those observed in Germany. Consistent with findings from European cohorts, our study confirmed that pregnancy‐associated hypertensive disorders, particularly preeclampsia, as well as complications such as preterm delivery, twin pregnancy and elective caesarean section, are substantial risk factors for HFPP. These results support previous research linking angiogenic imbalance to the pathogenesis of PPCM. Significant risk factors for HFPP included maternal pre‐pregnancy body mass index ≥35 [adjusted odds ratio (aOR) 2.04, 95% confidence interval (CI) 1.28–3.25, P = 0.003], history of maternal hypertensive disorder (aOR 2.44, 95% CI 1.22–4.88, P = 0.012), gestational hypertension without significant proteinuria (aOR 2.14, 95% CI 1.27–3.61, P = 0.004), preeclampsia (aOR 2.43, 95% CI 1.39–4.23, P = 0.002), type 1 or type 2 diabetes (aOR 3.27, 95% CI 1.66–6.45, P < 0.001) and twin pregnancy (aOR 2.74, 95% CI 1.37–5.49, P = 0.005). Additionally, extensive prepartum [odds ratio (OR) 2.86, 95% CI 1.18–6.98, P = 0.018] and postpartum blood loss (OR 2.50, 95% CI 1.44–5.02, P = 0.001) and maternal mental disorders (OR 7.39, 95% CI 4.10–13.31, P < 0.001) were significantly more common among HFPP patients. Conclusions The incidence of HFPP among women in Finland from 1996 to 2021 was low. HFPP exhibited a strong association with several risk factors, including preeclampsia, obesity, preterm delivery, twin pregnancy, elective caesarean section, multifoetal births, type 1 and type 2 diabetes, significant prepartum and postpartum blood loss and maternal mental health disorders. These findings underscore the importance of targeted interventions and careful monitoring in high‐risk groups to mitigate the impact of HFPP on maternal health.